2015
DOI: 10.1007/s10811-015-0743-x
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of microalgae from desert environments of Qatar

Abstract: The Qatar University Culture Collection of Cyanobacteria and Microalgae (QUCCCM) is a unique resource containing a diverse collection of microalgae and cyanobacteria, isolated from the Qatar desert environment. In order to ensure maximum preservation of this resource, a number of cryopreservation techniques were applied to various strains, and the preservation effectiveness (cell viability and lipid productivity) was determined. The conditions tested were direct, passive, and freeze-cooling cryopreservation (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
0
13
1
Order By: Relevance
“…3B ). Saadaoui et al (2016) confirmed that the lipid production could be affected by the cryopreservation method that could result in an increase and decrease in lipid content. When the two cryopreservants were compared, a higher lipid content was observed in the biomass that was cryopreserved with glycerol.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…3B ). Saadaoui et al (2016) confirmed that the lipid production could be affected by the cryopreservation method that could result in an increase and decrease in lipid content. When the two cryopreservants were compared, a higher lipid content was observed in the biomass that was cryopreserved with glycerol.…”
Section: Resultsmentioning
confidence: 64%
“…3A ). Saadaoui et al (2016) reported that Scenedesmus cells rapidly recover after 1 month of storage in liquid nitrogen using dimethyl sulfate as cryoprotectant. Microalgae exhibited differences in growth rate among different strains (ANOVA, F = 925.02, p < 0.001, d f = 3; post hoc in Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…R3 showed no significant difference in growth rate between before and after of cryopreservation, unlike other 2 strains. Saadaoui et al (2016) reported that Scenedesmus cells are rapidly recovered after 1 month storage in liquid nitrogen using dimethyl sulfate as cryoprotectant.…”
Section: Cryopreservation Testmentioning
confidence: 99%
“…However, high temperatures can severely affect the 14 productivity of said systems (Béchet et al, 2013). For this reason, it has become important the 15 isolation and characterization of high temperature-tolerant microalgal species in order to Chlorella and Scenedesmus (Silkina et al, 2017). However, wastewater has an elevated amounts 1 of nitrogen, phosphorus and microbes, which could affect algal productivity (Mara, 2004; 2 Mahapatra & Ramachandra, 2013) Therefore, an efficient strategy to mitigate potential negative 3 effects of the use of wastewater as culture media is the isolation of wild algal strains that 4 proliferate in it (Mahapatra & Ramachandra, 2013).…”
mentioning
confidence: 99%